Mean and visit‐to‐visit variability of glycated hemoglobin, and the risk of non‐alcoholic fatty liver disease - Jee Hee Yoo; Mira Kang; Gyuri Kim; Kyu Yeon Hur; Jae Hyeon Kim; Dong Hyun Sinn; Sang‐Man Jin (Journal of Diabetes Investigation, 2021)
Abstract Aims/Introduction We aimed to determine whether mean and visit‐to‐visit glycated hemoglobin (HbA1c) variability independently increase the incidence of non‐alcoholic fatty liver disease (NAFLD) across the diabetic continuum from normal glucose tolerance (NGT) to established diabetes. Materials and Methods In a longitudinal cohort study, 21,123 participants underwent five or more annual health screening checkups. Participants were categorized into diabetes (n = 1,635), prediabetes (n = 6,650) and NGT (n = 12,838) groups. Mean, standard deviation (SD) and coefficient of variation data on HbA1c were obtained from three consecutive measurements. The associations between those data and incident NAFLD were analyzed using Cox regressions. Results Over a median follow‐up period of 57 months, 3,860 (18.3%) participants developed NAFLD. The risk of NAFLD increased continuously, with the mean HbA1c beginning at 4.9%, even in the NGT group. We found a significant association between increasing HbA1c variability and incident NAFLD (coefficient of variation, adjusted hazard ratio 1.14, 95% confidence interval 1.01–1.29; standard deviation, adjusted hazard ratio 1.19, 95% confidence interval 1.05–1.36) in the diabetes group, but not in the NGT or prediabetes group. Consistent findings were observed when NAFLD patients with a low possibility of fibrosis were excluded. The association between the coefficient of variation of HbA1c and incident NAFLD in the diabetes group was significant only in those with an increasing trend of post‐baseline HbA1c (adjusted hazard ratio 1.24, 95% confidence interval 1.01–1.52). Conclusions Increased mean HbA1c levels elevated the risk of incident NAFLD, even with NGT. Increases in visit‐to‐visit variability of HbA1c independently elevated the risk of incident NAFLD, but only in the diabetes group.